Updating the classifier and educational programs for training personnel in the field of physical education and sport in the context of the transformation higher education system of Kazakhstan (Journal of Educational Sciences, 2021)
The article discusses the contradictions between the integration of higher education in Kazakhstan into the European educational space, the adaptation of the educational system of Kazakhstan to the provisions of the Lisbon Convention and the Bologna Declaration and the training of competitive specialists, on the one hand, and the existing methodological and practical limitations and shortcomings in the classifier of areas for training personnel with higher education. postgraduate education of the Republic of Kazakhstan in 2018 and educational programs in the field of physical education and sports, on the other hand. The purpose of this article is to analyze, generalize and systematize data and foreign practice based on regulatory legal acts and methodological documentation and search for possible solutions to improve the system of training personnel in the field of physical culture and sports in our country. The article provides examples of training personnel from other fields of science. The current educational programs of the register in the field of physical education and sports of the Kazakhstan are briefly analyzed. The theoretical arguments of this article serve as the basis for expanding the Kazakh classifier for training personnel in the field of physical culture and sports, and bridging the gap between the system of training personnel in higher education and the labor market. Key words: higher education, educational programs, physical education, classifier of programs, personnel training